PERBANDINGAN METODE TRUST-REGION DENGAN METODE NEWTON-RAPHSON PADA OPTIMASI FUNGSI NON LINIER TANPA KENDALA - Yully Estiningsih; farikhin farikhin (MATEMATIKA FSM, UNDIP, 2014)
Optimization is the best decision of the objective functions for produce a satisfactory solution. Optimization of multi variables unconstraints is to optimize the the objective functions which contains multi variable function freely without any specific requirements that restrict its function. Trust-Region methods methods is used to optimize multi variables unconstraint , Trust-Region methods quadratic approach of optimizing non linear the objective functions with a certain radius as the limit of the step size according to the quality of the approach. Newton-Raphson methods is a root search method with the the objective functions approaches a point, where the objective functions has a derivative. In this final will be talking about Trust-Region methods will compared with Newton-Raphson methods, and rendered example problem in which only be solved using Trust-Region methods.Keywords : Trust-Region Methods, Optimization, Newton-Raphson Methods